Novel injectable calcium phosphate bone cement from wet chemical precipitation method - Hablee, Sufiamie; Sopyan, Iis; Mel, Maizirwan; Mohd. Salleh, Hamzah; Rahman, Md Mujibur; Singh, Ramesh Kishore (IOP Publishing Ltd., 2017)
Calcium phosphate cement has been prepared via chemical precipitation method for injectable bone filling materials. Calcium hydroxide, Ca(OH)2, and diammonium hydrogen phosphate, (NH4)2HPO4, were used as calcium and phosphorus precursors respectively. The synthesized powder was mixed with water at different powder-to-liquid (P/L) ratios, which was adjusted at 0.8, 0.9, 1.0, 1.1 and 1.2. The influence of P/L ratio on the injectability, setting time and mechanical strength of calcium phosphate cement paste has been evaluated. The synthesized powder appeared as purely hydroxyapatite with nanosized and agglomerated spherical particles. All cement pastes show excellent injectability except for the paste with P/L ratio 1.2. Calcium phosphate cement with P/L ratio 1.1 shows the ideal cement for bone filler application with good injectability, the initial and final setting times of 30 min and 160 min, and the compression strength of 2.47 MPa. The result indicated that the newly developed calcium phosphate cement is physically suitable for bone filler application. This paper presents our investigation on the effect of P/L ratio on the handling and mechanical properties of calcium phosphate cement prepared via wet chemical precipitation method.